Pengaruh Disiplin dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan PT Anugerah Tridaya Mandiri Banyuasin - Edduar Hendri; Oktariansyah Oktariansyah; Aprizal Rosadian; Abdul Hamid Alif Habibi (Lembaga Dongan Dosen, 2025)
This study aims to analyze the influence of work discipline and job satisfaction on employee productivity at PT. Anugerah Tridaya Mandiri Banyuasin. The research employs a causal associative approach with a quantitative methodology. Data were collected through questionnaires distributed to 127 employees as research samples, and multiple linear regression analysis was used to examine the relationships between variables. The results indicate that work discipline has a positive and significant effect on employee productivity, with a regression coefficient of 1.306 and a significance value of 0.000. Conversely, job satisfaction negatively impacts productivity, with a regression coefficient of -0.410 and a significance value of 0.000. Simultaneous testing reveals that work discipline and job satisfaction collectively have a significant effect on productivity, contributing 96.3% to the variance in employee productivity. Therefore, improving work discipline and implementing more effective job satisfaction strategies are essential to enhancing employee productivity in the company.